1977
DOI: 10.1002/1097-0142(197703)39:3<1119::aid-cncr2820390317>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic squamous cell carcinoma of bronchus simulating giant cell tumor of bone

Abstract: A 57-year-old man underwent a right pneumonectomy for a bronchogenic carcinoma following bronchoscopy and bronchial biopsy. The tumor was a polypoid mass arising from the lower lobe bronchus. Microscopically it was characterized by mononuclear cells mixed with randomly distributed multinucleated giant cells similar to those seen in giant-cell tumor of bone. Also found were portions showing typical squamous cell and spindle cell carcinoma. Based on the light and electron microscopic findings, we suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Frequently these tumours have included a conventional carcinomatous element (Table 1) and therefore it has been suggested that the mesenchymal component is of Table 1 , Oyasu et al 1977, Posen 1981, Trepeta et al 1981, Esmaili et al 1983) although these observations do not exclude the possibility that the mesenchymal and epithelial components have a. separate origin, or that the epithelial component arises from the mesenchyme. However, the last possibility seems a distinctly unlikely explanation for the occurrence in our case of a giant cell tumour intimately associated with carcinoma in situ and, if this association is not mere coincidence, then it supports the concept of an epithelial derivation for osteoclastoma-like giant cell tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently these tumours have included a conventional carcinomatous element (Table 1) and therefore it has been suggested that the mesenchymal component is of Table 1 , Oyasu et al 1977, Posen 1981, Trepeta et al 1981, Esmaili et al 1983) although these observations do not exclude the possibility that the mesenchymal and epithelial components have a. separate origin, or that the epithelial component arises from the mesenchyme. However, the last possibility seems a distinctly unlikely explanation for the occurrence in our case of a giant cell tumour intimately associated with carcinoma in situ and, if this association is not mere coincidence, then it supports the concept of an epithelial derivation for osteoclastoma-like giant cell tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Over the decades, primary malignant pulmonary neoplasms containing giant cell components have been described in the literature . Some of these tumours have been designated as giant cell carcinomas, while others used the designation of primary choriocarcinomas of the lung for such lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Even though Hadley and Bullock appear to be the first to refer to the existence of primary carcinomas of the lung characterized by giant cells, it was not until Nash and Stout brought full awareness to the entity in 1958 by documenting five cases of primary carcinomas of the lung that they named giant cell carcinomas. Following the description by Nash and Stout, several other small series of this ‘new entity’ have been presented in the literature . Most of these publications attested to the presence of giant cells to which different characteristics were attributed either by morphological, ultrastructural or immunohistochemical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there have been only ten cases of pulmonary tumors with OGCs reported in the English literature (Table ), and this is the first report in which immunohistochemical and genomic studies were performed. Despite its unusual combination, all cases, including the current case have heterogeneous components.…”
Section: Introductionmentioning
confidence: 96%
“…Extraosseous tumors harboring OGCs have been most frequently reported in the pancreas, but also in the breast, liver, thyroid gland, urothelial tract, mesothelium and other locations. Only a few pulmonary tumors harboring OGCs have been reported . The great majority of previously reported pulmonary tumors harboring OGCs were associated with undifferentiated carcinoma including large cell carcinoma or carcinosarcoma, with only one case of differentiated adenocarcinoma associated with OGCs being reported in the literature, a case of mucinous adenocarcinoma with granulomatous and foreign body reaction .…”
Section: Introductionmentioning
confidence: 99%